2021
DOI: 10.3390/en14134043
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment Method Combining Independent Protection Layers (IPL) of Layer of Protection Analysis (LOPA) and RISKCURVES Software: Case Study of Hydrogen Refueling Stations in Urban Areas

Abstract: The commercialization of eco-friendly hydrogen vehicles has elicited attempts to expand hydrogen refueling stations in urban areas; however, safety measures to reduce the risk of jet fires have not been established. The RISKCURVES software was used to evaluate the individual and societal risks of hydrogen refueling stations in urban areas, and the F–N (Frequency–Number of fatalities) curve was used to compare whether the safety measures satisfied international standards. From the results of the analysis, it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The risk assessment of gas stations is linked to specific methods in the literature. The System Theoretic Accident Model and Processes [13] focuses on the extension of the causal principle of the safety nexus, the extended DEMATEL-STPA method and its application to hydrogen refueling stations [13], or the risk assessment of the location of a hydrogen refueling station in an urban area [14], or the use of the RISKCURVES software and the Layer of Protection Analysis method for the fire risk assessment of a hydrogen filling station in an urban area and also focusing on the applied the passive and active independent protection layers confirmed that these measures significantly reduced societal risk as well as individual risk and met international standards [15]. Another study used the Accident Risk Assessment Method for Industrial Systems (ARAMIS) [16] in conducted a risk assessment of the refueling area of a hydrogen-gasoline hybrid refueling station.…”
Section: Methodsmentioning
confidence: 88%
“…The risk assessment of gas stations is linked to specific methods in the literature. The System Theoretic Accident Model and Processes [13] focuses on the extension of the causal principle of the safety nexus, the extended DEMATEL-STPA method and its application to hydrogen refueling stations [13], or the risk assessment of the location of a hydrogen refueling station in an urban area [14], or the use of the RISKCURVES software and the Layer of Protection Analysis method for the fire risk assessment of a hydrogen filling station in an urban area and also focusing on the applied the passive and active independent protection layers confirmed that these measures significantly reduced societal risk as well as individual risk and met international standards [15]. Another study used the Accident Risk Assessment Method for Industrial Systems (ARAMIS) [16] in conducted a risk assessment of the refueling area of a hydrogen-gasoline hybrid refueling station.…”
Section: Methodsmentioning
confidence: 88%
“…To evaluate the major accident hazards of the chemical facilities, individual and societal risks that consider the population within the impact area of the major accident are used [2]. To calculate the effects of major accident to its surrounding, a large number of calculation models have been developed which are based on the physical and chemical properties of substances and physical behaviour in general, and on validation experiments for specific, often extreme process conditions.…”
Section: Major Accident Hazardsmentioning
confidence: 99%
“…Camila Correa-Jullian et al [8] used traditional QRA modeling tools, like failure mode and impact analysis, event sequence diagram and fault tree analysis, to sort out the data of liquid hydrogen storage system required for quantitative risk assessment. Park and colleagues [9] evaluated the potential individual and social hazards linked to hydrogen refueling stations through an examination of the safety effectiveness of their protective measures. Haugom et al [10] analyzed the influence of different leakage sizes on the final consequences based on the Bayesian model.…”
Section: Introductionmentioning
confidence: 99%